Explaining Post-Cold-War Civil Conflict among 17 Billion Models: The Importance of History and Religion - Michael Jetter; Rafat Mahmood; Christopher F. Parmeter; Andres Ramirez Hassan (Institute of Labor Economics (IZA), 2020)
Model uncertainty remains a persistent concern when exploring the drivers of civil conflict and civil war. Considering a comprehensive set of 34 potential determinants in 175 post-Cold-War countries (covering 98.2% of the world population), we employ stochastic search variable selection (SSVS) to sort through all 234 possible models. Looking across both cross-sectional and panel data, three robust results emerge. First, past conflict constitutes the most powerful predictor of current conflict: path dependency matters. Second, larger shares of Jewish, Muslim, or Christian citizens are associated with increased chances of conflict incidence and onset - a result that is independent of religious fractionalization, polarization, and dominance. Third, economic and political factors remain less relevant than colonial origin and religion. These results lend credence to several existing schools of thought on civil conflict and provide new avenues for future research.
Keywords: D74; Q34; Z12; F54; 330; civil conflict; civil war; stochastic search variable selection (SSVS); greed versus grievances; religion and conflict